1969
DOI: 10.1139/f69-138
|View full text |Cite
|
Sign up to set email alerts
|

Overwinter Survival of Wild Fingerling Brook Trout in Lawrence Creek, Wisconsin

Abstract: Overwinter survival of brook trout (Salvelinus fontinalis) from the 9-month-old fingerling stage to the 16-month-old yearling stage varied from 35 to 73% during 11 successive winters (1954–65). Mean survival through these first winters of life was 54%.Survival appeared to be independent of fingerling density most winters, and especially when September densities were less than 2200/km, as they were during 7 of 11 years. Overwinter survival tended to increase with an increase in mean length of fingerling stocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 3 publications
7
101
1
Order By: Relevance
“…This seasonal depletion pattern has been reported for other fishes (Reimers 1963, Hunt 1969, Post & Evans 1989, Thompson et al 1991 and demonstrates the importance of lipid reserves for fueling routine metabolism during winter. In the presence of food, both cohorts appeared to selectively deplete lipid reserves rather than to maintain or synthesize new lipids.…”
Section: Lipid Storage Patterns: Spring Vs Summer Cohortsupporting
confidence: 77%
“…This seasonal depletion pattern has been reported for other fishes (Reimers 1963, Hunt 1969, Post & Evans 1989, Thompson et al 1991 and demonstrates the importance of lipid reserves for fueling routine metabolism during winter. In the presence of food, both cohorts appeared to selectively deplete lipid reserves rather than to maintain or synthesize new lipids.…”
Section: Lipid Storage Patterns: Spring Vs Summer Cohortsupporting
confidence: 77%
“…Such a disadvantage in body size can have consequences at later selective episodes. For instance, because mass-specific energy content of juveniles increases with body size (e.g., Berg and Bremset 1998), smaller and later-emerging juveniles may experience higher winter mortality due to energy depletion than earlier-emerging juveniles (Hunt 1969;Cargnelli and Gross 1997;Hurst and Conover 1998;Schultz et al 1998). Moreover, within-cohort size differences may amplify over time due to growth depensation (Purdom 1974;Jobling 1985), eventually influencing life-history traits such as precocious maturation and age at seaward migration (Thorpe et al 1983;Thorpe 1989;Wright et al 1990;Jonsson and Jonsson 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of total phosphorus on survival of brown trout from age 0 to age 1 (Table 6) may reflect increased food availability for age-0 fish that subsequently enabled them to be in better condition before winter. Hunt (1969) observed that overwinter survival of fingerling brook trout in a Wisconsin stream generally increased when fingerlings were large. Brown trout from more fertile streams grew faster, became sexually mature earlier, exhibited higher fecundity at a given age and produced larger eggs than trout from less fertile systems (McFadden et al 1965).…”
Section: Local Influences On Population Dynamicsmentioning
confidence: 98%